Research Progress on Cyanobacteria Bloom Monitoring Methods and Driving Factors - Zhang, Qingzhu (International Journal of Natural Resources and Environmental Studies, 2025)
Cyanobacteria bloom is one of the most serious water ecological environment problems in the world and have large impact on public health and aquatic ecosystems worldwide. The harmful effects of algal blooms not only include reduced aesthetics and recreational opportunities, but more seriously, algal toxins are produced during the outbreak, killing plants and animals in the water, threatening the safety of drinking water and quality of life of local residents. Scientific and accurate inversion of the temporal and spatial changes of cyanobacteria bloom and comprehensive and in-depth analysis of the causes of cyanobacteria bloom outbreak are the current research focus. This paper describes the main monitoring methods of cyanobacteria bloom and the influencing factors of the outbreak. Finally, through the investigation and summary of the research status of cyanobacteria bloom at home and abroad, it analyzes the existing problems in the field of research status, and finally analyzes its future development trend in related directions.